2004
DOI: 10.1539/joh.46.87
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity and Chronic Toxicity in Mice and Rats Administered Vinyl Acetate Monomer in Drinking Water

Abstract: Carcinogenicity and Chronic Toxicity in Mice and Rats Administered Vinyl Acetate Monomer in Drinking Water: Yumi Umeda, et al. Japan Bioassay Research Center, Japan Industrial Safety and Health Association—Carcinogenicity and chronic toxicity of vinyl acetate monomer (VA) were examined in male and female Crj:BDF1 mice and F344/DuCrj Rats. Groups of 50 mice and 50 rats of each sex were orally administered VA in drinking water containing 0, 400, 2,000 or 10,000 ppm (g/g) VA for 104 wk. Squamous cell tumors were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…This would equate to an air concentration of 26 ppt for a 60 kg individual inhaling 20 m 3 /day. In contrast, lifetime inhalation and drinking water ingestion studies in rats have shown that VAM causes site of contact mucosal tumors of the nasal and upper digestive tract, respectively, but at air concentrations in the hundreds of parts per million and drinking water concentration in the low parts per thousand range [Bogdanffy et al, ,; Umeda et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…This would equate to an air concentration of 26 ppt for a 60 kg individual inhaling 20 m 3 /day. In contrast, lifetime inhalation and drinking water ingestion studies in rats have shown that VAM causes site of contact mucosal tumors of the nasal and upper digestive tract, respectively, but at air concentrations in the hundreds of parts per million and drinking water concentration in the low parts per thousand range [Bogdanffy et al, ,; Umeda et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of squamous cell carcinomas and papillomas in mice and rats induced by VA in the oral cavity as reported by Umeda et al (2004).…”
Section: Tablementioning
confidence: 94%
“…Results of a BMD analysis of the data from Umeda et al (2004) on the incidence of squamous cell carcinomas and papillomas in mice and rats induced by VA in the oral cavity using BMDS version 2.1.2. software and the default settings of extra risk, a Benchmark Response (BMR) of 10%, and a 95% confidence limit. Using the data reported by Umeda et al (2004) on squamous cell papillomas plus carcinomas for male and female mice and rats, a BMDL 10 of 440 mg/kg bw/day was calculated.…”
Section: Dose Species Gender Dose Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Although acetaldehyde is thought to be a genotoxic metabolite, a threshold dose appears to exist for vinyl acetate below which no tumor formation occurs (SCHER 2008). Chronic drinking water studies in rats (Umeda et al 2004) found a dose-dependent increase in carcinomas in the upper gastrointestinal tract of female rats at ≥ 400 ppm ("lowest observed adverse effect level", LOAEL = 31 mg/kg bw/day for female and 21 mg/kg bw/day for male rats, respectively), of which the latter was suggested to be used as POD for oral risk assessment (ECHA 2008;Health Canada 2008). A threshold mechanism for tumor formation in the gastrointestinal tract following oral administration seems, therefore, likely (ECHA 2008).…”
Section: Example 4: Vinyl Acetatementioning
confidence: 99%